Environmental Rights and Goods Protection in the Light of the Principle of Equal Access to Legal Proceedings and the Principle of Penal Responsibility - Joldžić, Vladan (Zbornik Instituta za kriminološka i sociološka istraživanja, 2008)
This text analyze fundamental question of environmental rights protection, starting from the necessity to possess equal right to access to legal proceedings, as well as to have adequate penal protection of this basic human right, not only in the territory of own state, but at the equal way at the territory of the state wherefrom arise endanger or offence of the environmental rights or goods.